Polyols Prepared from Ring-Opening Epoxidized Soybean Oil by a Castor Oil-Based Fatty Diol - Jing Zhang; Ji Jun Tang; Jiao Xia Zhang (International Journal of Polymer Science)
Several biorenewable vegetable oil-based polyols with different molecular weights and various hydroxyl functionalities were successfully prepared by ring-opening epoxidized soybean oil with a castor oil-based fatty diol. It was found that several factors, including reaction time, reaction temperature, and molar ratios between epoxidized soybean oil and castor oil diol, affect structures and rheology behaviors of the final polyols. Proton NMR, FT-IR, GPC, and rheometry results revealed that the hydroxyl functionalities, molecular weight, and viscosity of the polyols could be tailored by controlling the above-mentioned factors. Besides, the role of solvents in the epoxy ring-opening process was investigated as well.